Electrical and luminescence properties, and energy band structure of SrBi2-xErxNb2O9 multifunctional ceramics. Issue 21 (1st November 2021) - Zhang, Yuying; Chu, Ruiqing; Xu, Zhijun; Zhang, Shangzhou; Zhang, Chao; Li, Guorong
Abstract: SrBi2- x Er x Nb2 O9 ( x  = 0.00, 0.02, 0.04, 0.06, abbreviated as SBN- x Er) multifunctional ceramics were prepared by solid-phase reaction method. Thermal annealing behavior shows that SBN- x Er ceramics have stable piezoelectric properties. For sample with x  = 0.06, the piezoelectric constant d 33 at 400 °C close to its Curie temperature retains 80% of its room temperature d 33 value. Considering the luminescence characteristic of Er 3+ ions, samples possess bright up-conversion photoluminescence performance with the strong green emission band at 550 nm and the weak red emission band at 670 nm under 980 nm laser source. Moreover, the electronic band structure of SBN- x Er ceramics was calculated using first principles. It is found that Er 3+ doping causes the conduction band of samples to pass through the Fermi level and the valence band to be away from the Fermi level. The results suggest that SBN- x Er ceramics have good prospects in future luminescence and piezoelectric properties integrated devices.